A first-principles study of structural, electronic and optical properties of α-Te tubular nanostructures modulated by uniaxial strain. (1st May 2022) - Yang, Riyi; Chen, Yu-Yo; Guo, Yanrong; Shen, Hong; Wang, Songyou; Jia, Yu; Su, Wan-Sheng
Abstract: First-principles calculations were performed to study the effect of uniaxial strain on the electronic properties of α -Te nanotubes (NTs) of different configurations and tube sizes. Our ab initio molecular dynamics simulation and phonon dispersion calculation indicate that both armchair (5, 5) and zigzag (10, 0) α -Te NTs are thermodynamically stable and exhibit good dynamic stability at room temperature. Under compressive and tensile strains of ±10%, the atomic structure of the α -Te NTs remains stable, demonstrating they have good flexibility. An increase in uniaxial strain leads to a progressive decrease in the band gap for both armchair and zigzag α -Te NTs. Interestingly, it is found that armchair (5, 5) α -Te NTs experience an intriguing semiconductor–metal transition at a critical strain, while other α -Te NTs are semiconducting with an adjustable band gap. In addition, the valence band maximum and conduction band minimum charge density between the interlayers has an impact on the type of band gap in the (5, 5) and (10, 0) NTs. Finally, we found the optical properties can be significantly modulated under strain in the z direction. Increasing our understanding of the electronic and optical properties of α -Te NTs under strain modulation helps shed light on the properties of new nanomaterials more generally, paving the way for future optoelectronic applications. These findings highlight the tunable electronic and optical properties of α -Te NTs, which is promising for applications in nanodevices such as opto-electronics, electrical switches, and nanoscale strain sensors.